Efektivitas Model Pembelajaran Kooperatif Tipe Artikulasi terhadap Hasil Belajar Matematika Kelas VIII SMP - Ahmad Surya Wijaksono; Sri Subarinah; Nurul Hikmah; Syahrul Azmi (Griya Journal of Mathematics Education and Application, 2022)
This study aims to determine the effectiveness of the articulation type cooperative learning model on the mathematics learning outcomes of eighth grade junior high school students. The research design used was a quasi-experimental design with a post-test only control group design, namely the experimental subjects in the control class and the experimental class were not chosen randomly and the experimental class was given treatment using an articulation type cooperative learning model while the control class was not given any treatment. The population in this study were all eighth grade students of SMP Negeri 19 Mataram in the 2018/2019 academic year. The number of students in this population is 188 students spread over 6 classes. The sample was selected using purposive sampling technique and selected class VIII-A as the experimental class and VIII-B as the control class. The instruments used to obtain the data are student activity observation sheets and test questions used to obtain learning outcomes data. Statistical analysis of the data was carried out using the t-test at an error rate of 5%. The data obtained showed that the experimental class learning outcomes increased by 20.67% (from 54.2 to 74.87) while the control class learning outcomes increased by 16.34% (from 51.47 to 67.81). Statistical analysis of student learning outcomes obtained is 2.01 > 1.99. The results of the statistical analysis are supported by an increase in student activity at each meeting, namely in each meeting the students in the experimental class apply the articulation type cooperative learning model so that students are actively involved during the learning process.